Tuning acoustic performance of multi-chamber hybrid mufflers - Trinh, Van-Hai (Vietnam Journal of Mechanics, 2021)
In this paper, we investigate the functional acoustic performance of multi-chamber mufflers using a numerical approach. The wave propagation governing in expansion chamber domains is first introduced and solved by the finite element method. Our numerical results of selected muffler configurations are compared with the reference predictions model and experiments in order to validate the present procedure. Then, the influence of the geometry characteristics of typical and hybrid configurations of multi-chambered mufflers (number of sub-chambers, micro-perforated tube structure) on their sound transmission loss is studied. The obtained results indicate that the structure of the considered muffler has a strong effect on their acoustical performance, and the location and the high level of resonances of the sound transmission loss behavior are strongly related to the number of sub-chambers as well as micro-perforated tube characteristics. By tuning geometrical parameters (e.g., having a small perforation ratio), we enable to design mufflers having a higher sound transmission loss (up to 110 dB) at low frequencies (~ 195 Hz) but a constraint space (e.g., acoustic chamber length of 300 mm).